(untitled) (Communication & Society, 2014)
The universe of Art has been prone to resort to transtextuality and metalanguage since the beginning of the human activity. Films like Sunset Boulevard or Cinema Paradiso have shown the interest in the expression of the cinematographic praxis through its own tools. However, it is not frequent to find self-referential and transtextual language in the field of fake documentary; this is the case of The Unmaking of, an awarded movie made by Juan Manuel Chumilla Carbajosa which represents a step forward in metafiction since it is a self-referential film into the frame of a fake. A metalinguistic movie, unique in the Spanish cinematography, that deserves to be studied in depth.